Pedoman Pemulihan Pertanian dan Penguatan Ekonomi Wisata Pascabencana Banjir melalui Inovasi Geospasial, Hidroponik, dan Pemberdayaan Pemuda di Gampong Leles, Aceh Timur - Islami Zukya Rona; Zaidan Zikri Malem; Dini Ramadhani; Lailissa'adah Lailissa'adah (Universitas Pahlawan Tuanku Tambusai, 2026)
For The 2025 flood in Gampong Leles, East Aceh, caused a 50–60% decline in agricultural productivity and hindered local tourism economic development. This community service initiative aims to enhance community capacity through the application of adaptive hydroponics and the utilization of geospatial tools for post-disaster recovery. The methodology employed is Participatory Action Research (PAR), involving socialization, training, technological implementation, mentoring, and evaluation. Key partners include the Sara Datu Farmers Group Association (Gapoktan) and the Gampong Leles Youth Organization (Karang Taruna). The results indicate that more than 70% of the farmer group members are capable of applying basic hydroponic techniques, with 16 households adopting simple hydroponic systems. Furthermore, the program produced village administrative maps and tourism potential maps as a foundation for disaster-mitigation-based regional development. These activities have resulted in increased technical capacity, strengthened youth roles, and a more adaptive local economy. The integration of hydroponics, geospatial technology, and community empowerment has proven to be an effective model for sustainable post-disaster regional recovery